Comment on De Rosa et al. Hearing Loss: Genetic Testing, Current Advances and the Situation in Latin America. Genes 2024, 15, 178 - Elgoyhen, Ana Belen (2024)
The manuscript "Hearing Loss: Genetic Testing, Current Advances and the Situation in Latin America" by De Rosa et al. includes a comprehensive wealth of data that describe the state of the field in the Latin American region. A detailed demographic and economic landscape is presented, and provides insightful historical perspectives on key genetic advancements in hearing loss (HL) diagnosis. Nevertheless, the paper lacks important additional information concerning the current situation of genetic and genomic medicine in Latin American countries.